Training and Education on the Use of Wood Waste in the Furniture Industry Group in Karang Anyar Village - Firdasari; Andriani, Meri; Nova Purnama Lisa; Azwar Yusri; M. Iqbal Haikal (Amala Jurnal Pengabdian Kepada Masyarakat, 2023)
Wood waste is often found in several home furniture business locations in Langsa City, including in the furniture industry in Karang Anyar Village. The problem so far is that wood waste is not processed and utilized due to a lack of knowledge in processing wood waste into a product that has economic value and wood waste will also have a negative impact on the environment. The aim of this Community Service activity is to educate and provide training to furniture business groups to utilize sawdust waste into economically valuable products such as chipboard and blockboard. The activity method begins by coordinating with partners from the Karang Anyar Village furniture industry group totaling 12 people and then preparing the materials and tools used. The stages of making chipboard and blockboard with dimensions of 40x40x10 from wood waste are then the stage of training and education for the community and monitoring the results of activities. From the results of the activity, training participants received good benefits in understanding waste and the impacts that will arise from waste with a percentage of 45% and 70% with very good grades. However, for waste processing, the training participants only got a very good understanding of 30%. The skill of making particle board from wood waste increased after training by a percentage of 55% and participants benefited from the training by 70% for an excellent score.